Usability Evaluation Aplikasi Berbasis Website dengan Menggunakan Metode Importance Performance Analysis - Fajar Alam, Putra; Wulandari, Sari (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
The Ministry of Environment and Forestry provides an appeal to waste banks to use online systems in managing waste bank activities. The online system referred to is the online waste management system through the banksampah.id account. However, the level of activity of garbage banks in using the online system is relatively low (36.46%). Besides, in 2019, the Bandung City DLH has used banksampah.id as an application in evaluating the performance of waste banks. Therefore, this study was conducted aiming to evaluate the level of usability of banksampah.id so that it can be known aspects of banksampah.id that need to be improved. Evaluation of usability level is carried out using the Importance Performance Analysis (IPA) method. The usability evaluation results show that there are 7 usability attributes in the "Concentrate Here" category, 10 usability attributes in the "Keep Up The Good Work" category, 8 usability attributes in the "Low Priority" category and 9 usability attributes in the "Possible Overkill" category. Improvements to usability banksampah.id focus on 7 attributes categorized as "Concentrate Here" namely (1) availability of procedures for the use of various applications, (2) procedures for using applications that have been available easily understood by users, (3) completeness of customer profile, (4) availability of up-to-date customer data, (5) speed in data processing, (6) availability of communication features between Garbage Banks, and (7) availability of communication features between Garbage Banks and collectors.